SENTENCING GUIDELINES IN THE NATIONAL CRIMINAL CODE: IMPLEMENTATION IN JUDICIAL DECISIONS - Kurniasanti; Syukri Kurniawan (RADJA PUBLIKA, 2026)
Law Number 1 of 2023 concerning the Criminal Code introduces sentencing guidelines as an important component of the reform of Indonesia’s sentencing system. The introduction of these guidelines aims to control the use of judicial discretion, enhance rationality in sentencing decisions, and reduce sentencing disparities in criminal justice practice. This study aims to examine the concept of sentencing guidelines in the National Criminal Code and to analyze their implementation in judicial decisions. This research employs normative legal research using statutory and conceptual approaches. The results show that the sentencing guidelines in the National Criminal Code are systematically structured, covering general provisions, sentencing guidelines for individual offenders and corporations, guidelines for the application of imprisonment, as well as other provisions related to the implementation of punishment. These guidelines are not intended to restrict judicial independence but rather to provide a framework of consideration to ensure that sentencing decisions are based on rational, proportional, and just reasoning. The implementation of sentencing guidelines is expected to improve the quality of legal reasoning in judicial decisions, prevent irrational sentencing disparities, and strengthen public trust in the criminal justice system.